Implementasi Pendidikan Kewirausahaan Sebagai Character Building Mahasiswa Pendidikan Ekonomi UNPGRI Kediri - Zainal Arifin, Efa Wahyu Prastyaningtyas (Universitas PGRI Madiun, 2019)
Entrepreneurship is a course that aims to provide understanding and skills to students about entrepreneurs, in accordance with the learning objectives of being able to understand, analyze basic concepts of entrepreneurship and business ethics, create and use a trusted and effective business plan. This study aims to determine whether the implementation of entrepreneurship education affects the character building of UN PGRI Kediri economic education students in the practice of entrepreneurship, by looking at before and after getting KWU education whether it can generate character buliding for students. This study is classified as an experimental study using the Wilcoxon signed rank test design with one group pre test post test design. This study shows a positive result that entrepreneurship education has a significant effect on student character building.